"We don't routinely check vaccination background in adults": a national qualitative study of barriers and facilitators to vaccine delivery and uptake in adult migrants through UK primary care. Issue 10 (10th October 2022) - Carter, Jessica; Mehrotra, Anushka; Knights, Felicity; Deal, Anna; Crawshaw, Alison F; Farah, Yasmin; Goldsmith, Lucy Pollyanna; Wurie, Fatima; Ciftci, Yusuf; Majeed, Azeem; Hargreaves, Sally
Abstract : Objectives: Explore primary care professionals' views around barriers/facilitators to catch-up vaccination in adult migrants (foreign-born; over 18 years of age) with incomplete/uncertain vaccination status and for routine vaccines to inform development of interventions to improve vaccine uptake and coverage. Design: Qualitative interview study with purposive sampling and thematic analysis. Setting: UK primary care. Participants: 64 primary care professionals (PCPs): 48 clinical-staff including general practitioners, practice nurses and healthcare assistants; 16 administrative-staff including practice managers and receptionists (mean age 45 years; 84.4% women; a range of ethnicities). Results: Participants highlighted direct and indirect barriers to catch-up vaccines in adult migrants who may have missed vaccines as children, missed boosters and not be aligned with the UK's vaccine schedule, from both personal and service-delivery levels, with themes including: lack of training and knowledge of guidance among staff; unclear or incomplete vaccine records; and lack of incentivisation (including financial) and dedicated time and care pathways. Adult migrants were reported as being excluded from many vaccination initiatives, most of which focus exclusively on children. Where delivery models existed, they were diverse and fragmented, but included a combination of opportunistic and proactive programmes. PCPs noted that migrants expressed to them a range of views around vaccines, from positivity to uncertainty, to refusal, with specific nationality groups reported as more hesitant about specific vaccines, including measles, mumps and rubella (MMR). Conclusions: WHO's new Immunization Agenda 2030 calls for greater focus to be placed on delivering vaccination across the life course, targeting underimmunised groups for catch-up vaccination at any age, and UK primary care services therefore have a key role. Vaccine uptake in adult migrants could be improved through implementing new financial incentives or inclusion of adult migrant vaccination targets in Quality Outcomes Framework, strengthening care pathways and training and working directly with local community-groups to improve understanding around the benefits of vaccination at all ages.